Kontribusi Organisasi, Interpretasi, dan Aplikasi dalam Implementasi Kebijakan Kartu Identitas Anak (KIA) - Sutanto, Hari Prasetyo; Putra, Imam Radianto Anwar Setia (Research and Development Agency Ministry of Home Affairs, 2021)
The provision of Child Identity Card (KIA) services does not necessarily provide satisfactory results. This is seen from the realization of Pangandaran District's results, where a Birth Certiï¬cate's achievement reached 84 percent in 2019. But in terms of achievement, it is still very minimal; namely, 24 out of 12,224 are obliged to Child Identity Card (KIA). The study aims to explain the organization's contribution, interpretation, and application of the Child Identity Card policy. The study used a qualitative approach with a descriptive-qualitative analysis method utilizing data obtained from interviews with elements of executing agency ofï¬cials, cooperation agencies, stakeholders in six local governments with the analysis technique using reduction, display, and conclusion. The study results reveal that policy implementation from the organizational aspect of the Child Identity Card (KIA) policy focuses on cooperating with other agencies based on the principle of mutual beneï¬t. It is necessary to create a legal umbrella for cooperation and eliminate sectoral selï¬shness between government agencies. In the Interpretation aspect, it can be seen that the understanding of the implementing agencies and cooperative agencies on Child Identity Card (KIA) is very good because the rules are clear, technical, and implemented. However, it requires socialization speciï¬cally for Child Identity Card (KIA) services to be carried out evenly and extensively in the service area and targeting the community/target groups. In the application aspect, there is still misuse of ink, printing tools, and blanks. Continuity of cooperation is constrained by the lack of proï¬t (small scale), limitations on authority, and e-ID card issuance for local elections (politics). The conclusion on the implementation of the Child Identity Card (KIA) policy poses challenges to the ability of human resources as policy implementers and the availability of service delivery infrastructure. Besides, the top-down implementation of the Child Identity Card (KIA) policy coupled with limited resources has an impact on the achievements of local government policies.